Rancang Bangun Miniatur Pintu Gerbang Otomatis Berbasis NodeMCU ESP8266 Dengan Kendali Internet of Things - Wahyu Teguh Setiyawan; Lukman Aditya; Tri Ongko Priyono (Teknik Elektro Universtias Krisnadwipayana, 2025)
The warehouse gate is the most important front security component, usually has a very large and heavy dimension. So it takes power to open and close it. In the design research of a miniature automatic warehouse gate based on nodemcu esp8266 with internet of things control to make it easier to open and close the warehouse gate with an electronic circuit that can be controlled by a cellphone or laptop via the blynk application. To control the system on this miniature warehouse gate tool, NodeMcu ESP8266 is used as a center for data processing. The PIR sensor is used as a sensor to detect movement located in front of the gate. After that there is an IBT 2 module to control the voltage that will be forwarded to the drive motor and can also change the direction of motor rotation, a 12 v DC Gearbox motor as a driver for the warehouse gate, and there is a 16x2 LCD to display the process that occurs on the gate as output. The use of NodeMCU ESP8266 as a liaison between the Blynk application using an internet network with a maximum distance of 16 meters. The data results from the rotation of the DC motor in the process of opening the gate door are 185 rpm, in the process of closing the gate door 204 rpm and without being exposed to the load of the warehouse gate door 250 rpm, the voltage on the DC motor when rotating with an input voltage of 12.10 v and an output voltage of 4.76 v and the detection distance of the PIR sensor movement from a distance of 0 cm to 200 cm